Polymorphism of the PLIN1 gene and its association with body measures and ultrasound carcass traits in Qinchuan beef cattle - Raza, Sayed Haidar Abbas; Shijun, Li; Khan, Rajwali; Schreurs, Nicola M; Manzari, Zeinab; Abd El-Aziz, Ayman Hassan; Ullah, Irfan; Kaster, Nurgulsim; Shah, Mujahid Ali; Zan, Linsen (Genome, 2020)
The PLIN1 gene produces a phosphorylated protein wrapped in lipid droplets in adipocytes. This phosphorylation assists the mobilization of fat into adipose tissue. The purpose of the experiment was to study the polymorphism of the PLIN1 gene and its relationship with the body and carcass characteristics of Qinchuan cattle to find molecular genetic markers that can be used for breeding. The expression level of the PLIN1 gene was determined in various tissues by qRT-PCR. The results showed that the highest level of PLN1 expression was found in subcutaneous fat, followed by the heart and longissimus muscle, and the lowest level was found in the kidney. Five SNP loci of the PLIN1 gene were identified in 510 Qinchuan cattle, including g.3580T>C (SNP1), g.3898G>A (SNP2), g.8333G>A (SNP3), g.10517T>C (SNP4), and g.10538G>T (SNP5). The results show that SNP1, SNP2, SNP3, and SNP4 were moderately polymorphic (0.25 < PIC < 0.5), while SNP5 was minimally polymorphic (PIC < 0.25). SNP2, SNP3, and SNP5 were within Hardy-Weinberg equilibrium (P > 0.05), but SNP1 and SNP4 were not (P < 0.05). Correlation analysis showed that the five SNPs of the PLIN1 gene were correlated with back-fat depth, intramuscular fat, and chest depth of Qinchuan cattle. The double haplotype H2H4 in Qinchuan beef was associated with body and carcass traits. We conclude that variants mapped within PLIN1 can be used in marker-assisted selection for carcass quality and body traits in breed improvement programs for Qinchuan cattle.
Keywords: single nucleotide polymorphisms; genetické asociační studie; alely; Alleles; výpočetní biologie; velikost těla; Linkage Disequilibrium; mRNA expression; caractères de la morphologie corporelle; Gene Expression; Genotype; Body Weights and Measures; sekvence aminokyselin; Haplotypes; bovins Qinchuan; tělesné váhy a míry; body measurement traits; expression de l’ARNm; Genetic Variation; gène PLIN1; Polymorphism, Single Nucleotide; marker-assisted selection; haplotypy; vazebná nerovnováha; Animals; exprese genu; Polymorphism, Genetic; jednonukleotidový polymorfismus; Quantitative Trait, Heritable; Perilipin-1; Phenotype; sélection assistée par marqueurs; zvířata; Computational Biology; Cattle; polymorphismes mononucléotidiques; genetická variace; polymorfismus genetický; skot; fenotyp; Qinchuan cattle; PLIN1 gene; perilipin 1; Genetic Association Studies; Body Size; ženské pohlaví; genotyp; Quantitative Trait Loci; Female; kvantitativní znak dědičný; Amino Acid Sequence; lokus kvantitativního znaku